2013
DOI: 10.1177/0269881112473791
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa polyphenols enhance positive mood states but not cognitive performance: a randomized, placebo-controlled trial

Abstract: This study aimed to examine the acute and sub-chronic effects of cocoa polyphenols on cognition and mood. In a randomized, double-blind study, healthy middle-aged participants received a dark chocolate drink mix standardized to contain 500 mg, 250 mg or 0 mg of polyphenols (placebo) in a parallel-groups design. Participants consumed their assigned treatment once daily for 30 days. Cognition was measured with the Cognitive Drug Research system and self-rated mood with the Bond-Lader Visual Analogue Scale. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 24 publications
8
99
1
2
Order By: Relevance
“…Thus, caffeinated cocoa increased accuracy and reduced omission errors on the primary task of the Bakan test compared to cocoa alone stimuli at a rate of 60 per minute. Another study using a 500-mg cocoa drink showed results that appear to be generally consistent with the present findings, but two of three testing times were confounded by the post-cocoa consumption of a lunch [40], which reduces the ability to make meaningful comparisons to the calorie-free cocoa drink used here.…”
Section: Cocoa Versus Placebosupporting
confidence: 85%
“…Thus, caffeinated cocoa increased accuracy and reduced omission errors on the primary task of the Bakan test compared to cocoa alone stimuli at a rate of 60 per minute. Another study using a 500-mg cocoa drink showed results that appear to be generally consistent with the present findings, but two of three testing times were confounded by the post-cocoa consumption of a lunch [40], which reduces the ability to make meaningful comparisons to the calorie-free cocoa drink used here.…”
Section: Cocoa Versus Placebosupporting
confidence: 85%
“…A study by Pase et al (2013) showed that treatment of high dose of polyphenols from dark chocolate drink mix for 30 days signifi cantly increased self-rated calmness and contentedness relative to placebo. Acute testing was also conducted with mental health parameters were measured at baseline, and at 1, 2.5 and 4 hours after single dose.…”
Section: Discussionmentioning
confidence: 99%
“…48 They found that daily intake of dark chocolate, often reported to have positive effects on mood, decreased two specific products of gut microbial activity, hippurate and p-creso sulfate, though changes in subjective mood states were not reported. 49,50 In humans, the interaction between gastrointestinal and psychological symptoms is complex with microbiota playing dual roles in the modulation of both peripheral and central processes. Studies in healthy individuals and patients with irritable bowel syndrome indicate that probiotics or antibiotics can improve unpleasant digestive symptoms and it is likely that these symptom changes are dependent on both direct and indirect effects of the microbiota.…”
Section: The Pathways Of Microbiota-brain Interactionmentioning
confidence: 99%